Book review: Krastev, I. and Holmes, S. (2019). La luz que se apaga. Cómo occidente ganó la Guerra Fría pero perdió la Paz. Barcelona: Libros Debate. - Abreu-Colombri, José Antonio (2021)
"La luz que se apaga" focuses the attention on the period right after the ending of the Soviet Union which influenced the transformation of collective thinking. Neoliberalism, despite becoming the dominant philosophical idea with the victory of the capitalist systems, could not prevail as the only ideological system in the post-Cold War world.